1982
DOI: 10.1161/01.cir.65.6.1204
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of left ventricular contractility from late systolic stress-volume relations.

Abstract: SUMMARY The aim of the study was to determine if the end-systolic stress-end-systolic volume relation of the left ventricle (i.e., its tension-length relation) could be estimated from the analysis of a single yentriculogram. For that purpose, the left ventricular (LV) wall stress and volume were computed frame by frame in 35 patients (15 controls, 11 patients with valvular disease, six with coronary artery disease and three with congestive cardiomyopathy). In all patients, a linear relation was observed betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1983
1983
2006
2006

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Finally, alterations in LV volume, pressure, shape, and morphology are consistent with the increased peak systolic and diastolic wall stress reported in severe CAD (33,(132)(133)(134)164). Such increased wall stress would tend to alter myocardial energetic and mechanical performance.…”
Section: Myocardial Wall Stresssupporting
confidence: 71%
“…Finally, alterations in LV volume, pressure, shape, and morphology are consistent with the increased peak systolic and diastolic wall stress reported in severe CAD (33,(132)(133)(134)164). Such increased wall stress would tend to alter myocardial energetic and mechanical performance.…”
Section: Myocardial Wall Stresssupporting
confidence: 71%
“…These different methods remain valid for the equatorial region of the latter; however, they lead to systematic overestimation of the thickness of the left ventricular wall and underestimation of the radius of curvature (4), as we have reported in the normal subject (2). In myocardial infarction, Pouleur et al (21), in utilizing the Janz formula, found that the precision of the method decreases in the apical region of the left ventricle, where there are considerable variations in the radius of curvature. Our tridimensional approach allows the best possible assessment of the regional variations of the wall thickness and the radius of curvature in the three planes of space (2).…”
mentioning
confidence: 67%
“…The conspicuous reduction of contractil ity is therefore matched by an important recruitment of the preload, which allows ac ceptable performance of the pump [16,21].…”
Section: Aortic Insufficiencymentioning
confidence: 99%